Ultrasound-Assisted Versus Landmark-Guided Spinal Anesthesia in Patients With Abnormal Spinal Anatomy: A Randomized Controlled Trial. (March 2020) - Park, Sun-Kyung; Bae, Jinyoung; Yoo, Seokha; Kim, Won Ho; Lim, Young-Jin; Bahk, Jae-Hyon; Kim, Jin-Tae
Abstract : BACKGROUND: Spinal anesthesia using a surface landmark–guided technique can be challenging in patients with anatomical alterations of the lumbar spine; however, it is unclear whether using ultrasonography can decrease the technical difficulties in these populations. We assessed whether an ultrasound-assisted technique could reduce the number of needle passes required for block success compared with the landmark-guided technique in patients with abnormal spinal anatomy. METHODS: Forty-four patients with abnormal spinal anatomy including documented lumbar scoliosis and previous spinal surgery were randomized to receive either surface landmark–guided or preprocedural ultrasound–assisted spinal anesthesia. All spinal procedures were performed by 1 of 3 experienced anesthesiologists. The primary outcome was the number of needle passes required for successful dural puncture. Secondary outcomes included the success rate on the first pass, total procedure time, periprocedural pain scores, and the incidences of radicular pain, paresthesia, and bloody tap during the neuraxial procedure. Intergroup difference in the primary outcome was assessed for significance using Mann-Whitney U test. RESULTS: The median (interquartile range [IQR; range]) number of needle passes was significantly lower in the ultrasound group than in the landmark group (ultrasound 1.5 [1–3 {1–5}]; landmark 6 [2–9.3 {1–15}]; P < .001). First-pass success was achieved in 11 (50.0%) and 2 (9.1%) patients in the ultrasound and landmark groups, respectively ( P = .007). The total procedure time, defined as the sum of the time for identifying landmarks and performing spinal anesthesia, did not differ significantly between the 2 groups (ultrasound 141 seconds [115–181 seconds {101–336 seconds}]; landmark 146 seconds [90–295 seconds {53–404 seconds}]; P = .888). The ultrasound group showed lower periprocedural pain scores compared with the landmark group (ultrasound 3.5 [1–5 {0–7}]; landmark 5.5 [3–8 {0–9}]; P = .012). The incidences of complications during the procedure showed no significant differences between the 2 groups. CONCLUSIONS: For anesthesiologists with experience in neuraxial ultrasonography, the use of ultrasound significantly reduces the technical difficulties of spinal anesthesia in patients with abnormal spinal anatomy compared with the landmark-guided technique. Our results can lead to practical suggestions that encourage the use of neuraxial ultrasonography for spinal anesthesia in such patients.